Earthen Architecture in Seismic Zones: Latin America and the Pacific Fire Belt - Cuitiño Rosales, Maria Guadalupe (2021)
This paper analyzes the current state of earthen constructions in countrieslocated in the Pacific Ring of Fire. In Latin America, countries such asColombia, Ecuador, Peru, Bolivia, Chile and Argentina are located in thePacific Ring of Fire and are subject to strong seismic exposure, makingearthen constructions more vulnerable. From an analysis of the housingcensuses of each country, it was observed that currently, earthen constructioncontinues to be a construction option, that the percentage of earthenconstructions varies from country to country, and that they make up a highpercentage of dwellings; namely, in Colombia 5.3% (714.478 houses),Ecuador 8% (383.086), Peru 31% (2.390.625), Bolivia 37% (1.037.473),Chile 2% (121.756) and 1.9% in Argentina (230.185 houses). Peru, despitebeing one of the countries with the highest seismic risk, is the country withthe highest number of earthen dwellings. It was concluded that in all thecountries analyzed, earthen architecture prevails, employing different constructiontechniques whose characteristics are deeply rooted in each country’sancestral culture. This highlights the importance of having regulationsin place and skilled workers in order to intervene correctly and repair thestructures after a seismic event.